A new method for scour monitoring based on fiber Bragg grating. (October 2018) - Ding, Yong; Yao, Qingxiong; Zhang, Zhendong; Wang, Xin; Yan, Tengteng; Yang, Ye; Lv, Hui
Abstract: This paper introduces feasibility study of scour depth determination based on lateral soil pressure measurement. The method is used for sensors which are made of fiber Bragg grating (FBG) as the sensing element, where the front side is under soil pressure, and the back is under the water pressure. It can accurately monitor the lateral earth pressure by measuring the front and back of the pressure difference. The pressure in the horizontal direction is only water pressure in water, while it consists of lateral earth pressure and pore water pressure in the soil. Therefore the depth of the mud surface can be calculated by a plurality of sensors at different depth. The method can feedback erosion and siltation of hydraulic structure in time, and provide reliable data support for the safe operation of the hydraulic structure.